Produção de penicilina G acilase por organismos geneticamente modificados - Escallón, Ana María Vélez (2013)
Penicillin G acilase (PGA) is a key enzyme in the industrial production of β-lactamic antibiotics. In this work, it was studied the production of PGA from Escherichia coli by recombinant E. coli and from Bacillus megaterium by recombinant B. megaterium. In E. coli, the enzyme accumulates in the periplasmic cell space, B. megaterium secretes PGA, what may reduce downstream costs. With E.coli, the study has begun at the expression step. Using a donated recombinant microorganism, it was studied, in shake flasks cultures, the influence of temperature (ranging from 18 to 28°C) during induction phase in the PGA production. High level expression of PGA E. coli was detected at 20°C, which was 4-fold superior than the volumetric enzymatic activity reached at 28°C. Fed-batch cultures were conducted with glycerol as carbon source, using both defined and complex media as well as IPTG and lactose as inducers. Final biomass concentrations of 100 gDCW/L and 120 gDCW/L and enzymatic activity 210000 and 80000 IU/L were achieved, for complex and defined media, respectively. The study with B. megaterium was initiated isolating the pac gene, encoding for PGA from B. megaterium ATCC14945, which was after cloned into the pLipAhp expression plasmid, together with the promoter gene and a gene codifying antibiotic resistance. This construct (pga-pLipAhp) was used to transform three different B. megaterium strain protoplasts, aiming studies to determine the best expression host in terms of PGA production. The tested strains, B. megaterium PV361, QM B1551 and ATCC 14945, have respectively shown about 95%, 95% and 10% plasmidial stability, after eight consecutive growths. The best PGA production was detected in PV361. Study of thermal and pH stability with the purified enzyme showed that PGA has a half-life of 5 min at 60° C, 20 min at 50° C, keeping 100% of activity for 1h at pH 10.0 and up to 8 h at pH 5.0. The values of temperature and pH for maximum PGA activity are 37° C and 8.0, respectively. The enzyme was stable at least for 5 hours in these conditions, with Michaelis-Menten estimated as Km=8.8 μM. A systematic study was developed to search the best condition to obtain the highest level of B.megaterium PGA production by recombinant B.megaterium. Media compositions for biomass and PGA production were evaluated using a genetic algorithm. The screening was carried out in 96 microtiter deep well plates, starting as a minimal medium and studying the concentration of 12 defined components. In 7 generations, 240 different kinds of media were tested for production and secretion and a 10-fold increase in PGA production and 5-fold increase in biomass compared to the previously used minimal medium could be achieved. It was scaled-up to shaker flasks obtaining 3-fold in PGA production and 1.8-fold in biomass. Later, it was scaled-up to bioreactors obtaining 3-fold in biomass and 8-fold in PGA production. Using glycerol as carbon source, it was tested different complex amino acids sources, using flask cultures. The best medium was scale-up in a 5 L bioreactor, in a batch culture with pulses. The highest production of PGA of recombinant B. megaterium achieved was 105600 IU/L and 36 gDCW/L.